Evolution of Cluster Alignments as Evidence of Large-scale Structure Formation in the Universe - West, Michael J.; De Propris, Roberto; Einasto, Maret; Wen, Z. L.; Han, J. L. (American Astronomical Society, 2026)
The Universe's large-scale structure forms a vast, interconnected network of filaments, sheets, and voids known as the cosmic web. For decades, astronomers have observed that the orientations of neighboring galaxy clusters within these elongated structures are often aligned over separations of tens of Mpc. Using the largest available catalog of galaxy clusters, we show for the first time that cluster orientations are correlated over even larger scales-up to 200-300 comoving Mpc-and such alignments are seen to redshifts of at least z similar or equal to 1. Comparison with numerical simulations suggests that coherent structures on similar scales may be expected in Lambda CDM models.